Automatic Vibration Device For Stroke Patients - Mohamed Aminuddin, Mai Mariam; Mohamad Tarmizi, Noor Huda Hazirah (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
Permanent paralysis due to stroke could be avoided if they do some exercises on the affected limbs to keep the flowing of the blood and soften the muscle. Every treatment or exercise needs to be done periodically and requires the help of a normal person such as nurses or physiologists. However, a caretaker may not be able to provide 100% of the assistance to those stroke patients. Therefore, an automatic device that can provide a periodic exercise could help stroke patients in their recovery process with minimal participation of caretaker. However, the available machine that can accommodate such services is bulky and costly. It exercises the whole body, and this is not beneficial if the stroke only effect to some part of them body. Hence, this study had shown that Theory of Inventive Problem Solving approach is able to reduce the size of the machine but gives significant impact on the specific limbs. The findings could be used as foundation for stroke rehabilitation development system